Validation of an in-line non-destructive headspace oxygen sensor. (September 2016) - Cocola, L.; Allermann, H.; Fedel, M.; Sønderby, S.; Tondello, G.; Bardenstein, A.; Poletto, L.
Highlights: TDLAS sensor for package headspace gas analysis. In-line headspace gas testing for food packaging. Sensor calibration and performance evaluation. Abstract: Measurement and control of the gas composition of packaging headspace in situ is required by food and packaging industries. Contactless non-destructive Tunable Diode Laser Absorption Spectroscopy (TDLAS) gas sensors have been recently developed to enable real time in-line headspace characterization in a wide range of sealed food packaging. The objective of this work is to validate a new optical method versus existing destructive oxygen sensing methods that are standard for the industry. For this purpose, oxygen concentration measurements have been carried out in the same packaging samples using both the TDLAS gas sensor and a calibrated, intrusive sensor. The intrusive sensor has been assumed to estabilish the reference oxygen concentration data. Different types of packaging have been used for the validation measurements. The measurements have been implemented with different data integration times. The obtained results show that the TDLAS optical sensor is capable of non-destructive measurements of oxygen concentration in such common samples as flow-pack bags with an accuracy of 0.2 vol.% during one second.